Impacts of hazardous metals and PAHs in fine and coarse particles with long-range transports in Taipei City. (July 2019) - Hsu, Chin-Yu; Chiang, Hung-Che; Chen, Mu-Jean; Yang, Tzu-Ting; Wu, Yuh-Shen; Chen, Yu-Cheng
Abstract: This study assessed the impact on air quality and health risk by long-range transported (LRT) PM2.5-10 - and PM2.5 -bound metals and PAHs in Taipei City, Taiwan. Several methods with receptor aerosol measurements were used to quantify the effect of LRT. The hybrid single particle lagrangian integrated trajectory model (HYSPLIT) was used in conjunction with the potential source contribution function (PSCF) to distinguish the LRT aerosols. By using a general linear model (GLM) with a marginal mean and positive matrix fraction (PMF), this study also evaluated the annual increased level of LRT ( AIR LRT ) for each source contribution to the concentration and the resultant health risk of particle-bound metals and polycyclic aromatic hydrocarbons (PAHs). The LRT influenced fine-sized metals and PAHs rather than coarse-sized ones. We found that the level of PM2.5 -bound toxic metals (Pb, Cd, and As) and PAHs (Benzo[a]pyrene and dibenzo[ a, e ]pyrene) could increase by 90% under the influence of LRT in 2014, while an AIR LRT value of 25% for the PM2.5 mass concentration was observed. Overall, the excess cancer risk (ECR) resulting from PM2.5 -bound metal and PAH exposures was 6.40 × 10 −5 in relation to coal combustions (20.7%), traffic-related emissions (59.7%) and re-suspended aerosols (19.6%). Among these contributors, LRT-related metals and PAHs in PM2.5 accounted for 51% of the total ECR. Graphical abstract: Image 1 Highlights: Evaluating long-range transported (LRT) PM2.5-10 - and PM2.5 -bound metals and PAHs. The LRT influenced fine-sized metals and PAHs rather than coarse-sized ones. The level of PM2.5 -bound toxic metals and PAHs increase by 90% as a result of LRT. The LRT-related metals and PAHs resulting in potential health risk were addressed. Abstract : The impact of fine-sized metals and PAHs from long-range transport aerosol on air quality and human health risk in Taipei was evaluated.